2020
DOI: 10.1371/journal.pone.0228927
|View full text |Cite
|
Sign up to set email alerts
|

National TB program shortages as potential factor for poor-quality TB care cascade: Healthcare workers’ perspective from Beira, Mozambique

Abstract: Background Mozambique is one of the countries with the deadly implementation gaps in the tuberculosis (TB) care and services delivery. In-hospital delays in TB diagnosis and treatment, transmission and mortality still persist, in part, due to poor-quality of TB care cascade. Objective We aimed to assess, from the healthcare workers' (HCW) perspective, factors associated with poor-quality TB care cascade and explore local sustainable suggestions to improve inhospital TB management. Methods In-depth interviews a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
2
9
0
1
Order By: Relevance
“…The main health system-related barrier was that the TB diagnostic laboratory was at the municipal hospital which is distant from most rural health facilities, and clients cannot afford the transport cost [ 18 ]. Limited access to diagnostic facilities, mostly in rural settings, and long travel distance were similar barriers experienced by presumed TB clients in other parts of the world [ 6 , 7 , 22 26 ]. The lack of a standard referral system in our rural study facilities also led to extended waiting times for some referred clients at the municipal hospital and this further underscored their reluctance to go to the municipal hospital for further assessment and testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main health system-related barrier was that the TB diagnostic laboratory was at the municipal hospital which is distant from most rural health facilities, and clients cannot afford the transport cost [ 18 ]. Limited access to diagnostic facilities, mostly in rural settings, and long travel distance were similar barriers experienced by presumed TB clients in other parts of the world [ 6 , 7 , 22 26 ]. The lack of a standard referral system in our rural study facilities also led to extended waiting times for some referred clients at the municipal hospital and this further underscored their reluctance to go to the municipal hospital for further assessment and testing.…”
Section: Discussionmentioning
confidence: 99%
“…HCWs in the rural health facilities and those in the chest clinic of the municipal hospital perceived that if there was a team regularly supervising and monitoring the activities of HCWs then that would prompt them to ask about cough and request for sputum test where necessary. Lisboa et al in their study in Mozambique found that the lack of a motivated TB taskforce to supervise and monitor TB control activities in the health facility was a potential factor contributing to poor quality TB care [ 26 ]. In addition, HCWs in our study were of the view that if TB teams from the district, regional or national levels regularly visited the health facilities to monitor and encourage staff, this appreciation of their efforts combined with knowing their activities are going to be monitored would serve as a motivation for them to pay attention to TB case detection.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Study findings on TB/HIV co-infection align with similar studies in Mozambique and elsewhere on the continent. [16][17][18][19] Reasons for this may include the interaction between the two diseases in worsening each other's progress, suboptimal HIV management during the TB episode (low CD4 T-cell counts, high viral load, and increased risk of opportunistic infections), and increased drug burden to the co-infected patient. [16][17][18][19] The high TB/HIV prevalence and increased risk of poor TB treatment outcomes in this population highlight the importance of TB screening and preventive treatment in patients living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Reasons for this may include the interaction between the two diseases in worsening each other's progress, suboptimal HIV management during the TB episode (low CD4 T-cell counts, high viral load, and increased risk of opportunistic infections), and increased drug burden to the co-infected patient. [16][17][18][19] The high TB/HIV prevalence and increased risk of poor TB treatment outcomes in this population highlight the importance of TB screening and preventive treatment in patients living with HIV. [1] The treatment success rate in the study was well above the End TB Strategy target and in line with the 93% rate reported for 2018 by the NTP as well as in other similar local studies.…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio de la cascada de atención de la TB desde la perspectiva de los trabajadores de la salud en un entorno hospitalario indicó que la escasez de personal de enfermería tiene consecuencias negativas en la calidad de la atención (31). Lo anterior permite reflexionar que estas dificultades de los trabajadores de la salud son más marcadas en contextos de atención primaria de difícil acceso como en la presente investigación.…”
Section: "…El Anterior Año Fue Un Poco Complicado Porque Ni El Pacienunclassified